Leukocyte and Platelet Characteristics of the Giant Panda (Ailuropoda melanoleuca): Morphological, Cytochemical, and Ultrastructural Features - Kehoe, Spencer P.; Stacy, Nicole I.; Frasca, Salvatore; Stokol, Tracy; Wang, Chengdong; Leach, Kathryn Strayer; Luo, Li; Rivera, Sam (Frontiers in Veterinary Science, 2020)
The giant panda (Ailuropoda melanoleuca) is a vulnerable species and a charismatic member of zoological collections worldwide. Despite its importance as a representative species for global wildlife conservation efforts, no studies to date have described normal cell morphology or cytoplasmic constituents by traditional techniques such as cytochemical staining and evaluation of ultrastructural features. The objective of this study was to accurately identify and characterize the leukocytes and platelets of clinically healthy giant pandas using routine Wright-Giemsa stain, eight cytochemical stains, immunocytochemistry (CD3), and transmission electron microscopy (TEM) to further the collective understanding of normal cellular morphological features, cytochemical reactivity, and cytoplasmic contents found in health. Voluntary venipuncture was performed on four healthy individual animals (two adults and two juveniles), as part of routine preventive health evaluation. Blood was collected for routine and cytochemical stains, and into 2.5% glutaraldehyde for TEM. On Wright-Giemsa-stained blood films, leukocytes were differentiated into granulocytes (neutrophils, eosinophils, basophils) and mononuclear cells (lymphocytes, monocytes). Cytochemical staining revealed similar leukocyte and platelet staining patterns to those reported in other mammals, with some notable differences. By TEM, leukocytes with nuclear and cytoplasmic features of mononuclear cells were readily differentiated from granulocytes, and platelets had similar ultrastructural features to those reported in other mammals. Neutrophils were the predominant cell type followed by lymphocytes, while basophils were rare. Rare large or reactive lymphocytes, rare reactive monocytes, and rare large platelets were noted in apparently healthy giant pandas of this study. A unique mononuclear cell, with a moderately indented nucleus and shared cytochemical and ultrastructural characteristics of lymphocytes and monocytes, was discovered in this species. The combined cytochemical, immunocytochemical (CD3), and ultrastructural features of these unique cells more closely resemble those of monocytes, but the definitive cell lineage remains unknown at this time. This study provides novel information on giant panda leukocyte morphology and cellular constituents in health, shows the importance of manual blood film review, has important implications for hemogram interpretation in future clinical cases and research, and provides a baseline for future characterization and understanding of hemogram changes in response to disease.